2019
DOI: 10.1371/journal.pone.0219394
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of metformin on progression of benign prostate hyperplasia: A nationwide population-based cohort study in Korea

Abstract: Metformin, a first-line treatment for type 2 diabetes mellitus (T2DM), has recently been recognized for its pleotropic anti-proliferative, anti-cancer, and anti-aging effects. Contrary to the studies characterizing metformin effects in prostate cancer, little is known about these effects in BPH progression. With the Sample Cohort DB data during 2007 and 2017 from the Health Insurance Review and Assessment Service (HIRA) in South Korea, we investigated the preventative effect of metformin on BPH progression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In humans, an earlier retrospective cohort study conducted in the USA did not find any association between thiazolidinediones or metformin (adjusted HR for metformin use, 0.99; 95% CI, 0.94–1.03) and BPH while compared to sulfonylureas [ 87 ]. However, a later retrospective cohort study conducted in Korea using the Health Insurance Review & Assessment Service suggested that diabetes patients who used metformin had a reduced risk of BPH progression indicated by the occurrence of prostatectomy during follow-up while compared to a group without T2DM (HR, 0.86; 95% CI, 0.77–0.96; p=0.007) [ 88 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…In humans, an earlier retrospective cohort study conducted in the USA did not find any association between thiazolidinediones or metformin (adjusted HR for metformin use, 0.99; 95% CI, 0.94–1.03) and BPH while compared to sulfonylureas [ 87 ]. However, a later retrospective cohort study conducted in Korea using the Health Insurance Review & Assessment Service suggested that diabetes patients who used metformin had a reduced risk of BPH progression indicated by the occurrence of prostatectomy during follow-up while compared to a group without T2DM (HR, 0.86; 95% CI, 0.77–0.96; p=0.007) [ 88 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…Similarly, Hankinson et al ( 15 ) reported that metformin treatment in patients with type 2 diabetes reversed metabolic conditions by decreasing the androgen levels, thereby leading to high levels of androgen stimulating prostate growth, proliferation and tumorigenesis. Although the antitumor properties of metformin are not obvious in the early stages of prostate cancer development, the drug could be effective in decreasing the mortality of patients with prostate cancer by significantly improving the parameters of metabolic syndrome after ADT, and it could exhibit a therapeutic effect on some patients with asymptomatic or mild metastatic CRPC ( 23 , 24 ). There is potential for metformin to be used as a monotherapy or an adjuvant agent in ADT, or in external therapy or other chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the estrogen-β receptor, the pro-apoptotic response was increased. Results of this study are very promising, but more research is needed to rule out the effects of other medications used by patients and other confounding factors [14].…”
Section: Organ Systemsmentioning
confidence: 91%